PENGGUNAAN METODE FOUNTAIN UNTUK PENGEMBANGAN SISTEM INFORMASI ADMINISTRASI BANTU PKK (STUDI KASUS: PKK KELURAHAN SUMAMPIR) - Hellyana, Corie Mei; Pratama, Eva Argarini (Universitas Teknokrat Indonesia, 2025)
Family Empowerment and Welfare Group (PKK) is an organization that focuses on improving the social and economic welfare of families in Indonesia through various empowerment programs. Given the widespread use of smartphones, especially among PKK members, this study aims to explore the potential of a mobile-based administration system to address the existing challenges. This study focuses on the design and development of a smartphone application prototype to support PKK administrative tasks. To achieve this, the fountain method can be applied as a development approach, emphasizing continuous development and iterative testing. The resulting prototype is designed to simplify the administration process of PKK activities, making them more efficient and accessible. This study concludes that adopting a mobile-based solution can significantly improve the management of PKK activities, allowing for better data recording, reporting, and overall organizational coordination. Further development and testing stages are needed to refine the application and ensure its compatibility with the broader needs of the organization, although in the testing and implementation itself the results of the existing feature testing are 100% valid according to the expected results and the application can be used easily by early/beginner users because with the PKK administration information system application, PKK cadres can access the application from anywhere and anytime, this can be seen in the results of filling out the questionnaire at the trial and socialization stage that has been done previously with the results of 22.3% of users feeling quite satisfied, 67.1% satisfied and 10.6% very satisfied in the socialization and use of the application. The research findings emphasize the importance of technology adaptation in community-based organizations such as PKK, highlighting the potential benefits of a more modern administrative approach through mobile technology. This prototype serves as a basis for further development to increase the efficiency and capacity of the PKK organization.